Polymorphisms in CYP2D6 may predict methamphetamine related heart failure. (August 2013) - Sutter, M. E.; Gaedigk, A; Albertson, T. E.; Southard, J.; Owen, K. P.; Mills, L. D.; Diercks, D. B.
Abstract: Background . Methamphetamine (METH) has been associated with a dilated cardiomyopathy. The first and rate-limiting step of metabolism is dependent on the polymorphic enzyme CYP2D6. Objectives. To evaluate if polymorphisms in CYP2D6 can be associated with the development of a methamphetamine-induced cardiomyopathy. Methods . We performed a prospective case-control pilot study. Cases were defined by a urinary drug screen positive for amphetamine and evidence of heart failure by beta natriuretic peptide (BNP) greater than 300 pg/ml and symptoms of heart failure. Controls were defined with urinary drug screens positive for amphetamines but without evidence of heart failure defined by a BNP lesser than 300 pg/ml or symptoms of heart failure. Exclusion criteria were less than 18 years or greater than 60 years of age, urinary toxicology screen positive for additional stimulants, known coronary artery disease (CAD) defined by greater than 50% stenosis on catheterization or previous myocardial infarction, known cardiomyopathy of alternative etiology or inability to provide consent. Patients underwent gas chromatography confirmation-mass spectroscopy for methamphetamine, genotyping of CYP2D6, limited echocardiography, and participated in a modified 2007 National Survey of Drug Use and Health Stimulant Survey. Genotype results were analyzed with traditional classifications and "Activity Scores". Results . Fifty-six patients completed the study with 19 cases and 37 controls. There was no statistically significant difference in days of use in a month, age, gender, or ethnicity between cases and controls. While not statistically significant, age and days of use did trend higher in cases. CYP2D6 genotype demonstrated that the lower the activity score/poor metabolizer group had less heart failure than extensive metabolizers/higher activity score. However, it did not reach statistical significance. When adjusting for higher days of use, extensive metabolizers had the highest odds of developing a dilated cardiomyopathy. (OR: 2.33, 95% CI: 0.54–10.13). Echo findings in all cases showed reduced ejection fractions with a mean of 18.6% (range: 10–35%) and 70% had a dilated cardiomyopathy. No cardiomyopathies were seen in the controls. Mean ejection fraction was 56.75% (range: 45–70%). The odds ratio of having a dilated cardiomyopathy in extensive metabolizers was 1.62 (95% CI: 0.47–5.5). Conclusion . Our study demonstrates a trend that individuals with decreased metabolic activity were less likely to develop heart failure. While not statistically significant, a signal is present that extensive metabolizers may be at increased risk for the development of a cardiomyopathy.